The Changes of Myocardium in Minipigs after Coronary Vein Ligation Observed by Transmission Electron Microscopy - Wang, Juntao; Yu, Haijia; Song, Huihui; Yang, Yapan; Zhang, Leiming; Luo, Hongxing; Chen, Panpan; Chu, Yinjie (Journal of Cardiovascular Medicine and Cardiology, 2017)
Background: The study of coronary artery disease has been quite thorough. But there is few study on coronary vein disease. In clinical practice, some patients have suspicious symptoms of coronary artery disease without any evidence of coronary artery spasm, but coronary angiography showed no obvious stenosis in coronary artery. It may have relationship to coronary venous dysfunction. This study aims to develop a coronary vein ligation model, to investigate the effect of coronary vein occlusion on myocardial cells in normal miniature pigs. Methods: Adult minifies were divided into control group and intervention group. The coronary venous occlusion model was made by clamping the central vein. Myocardium was isolated from the myocardium and the myocardium was observed by transmission electron microscopy. Results: There were no significant changes in the sham operation group (control group). Mitochondrial edema, cristae broken, hyperplasia and auto phage some appeared in the operation group (intervention group). Conclusion: The ligation of the coronary vein causes dysfunction of myocardial cells. It gives us inspiration, coronary vein occlusive disease may be underestimated. It may be some causes of angina for patients with normal coronary angiography.